Development of Interactive Learning Media Based on Motion Graphic Animation for Basic Photography Subject - Yayang Yusmaningsih; Vera Irma Delianti; Lativa Mursyida; Rizkayeni Marta (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This study aims to design and develop interactive multimedia-based learning media utilizing motion graphic animation for the Basic Photography subject at SMK Negeri 4 Padang. This media was designed to assist students in understanding the material more effectively and engagingly. The method used is the Multimedia Development Life Cycle (MDLC), consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. The validity test involved four experts, two media experts, and two material experts, while the practicality test involved ten students from Class X DKV A. The results of the validity test show that the learning media is highly valid, with Aiken's V score of 0.94 for both media and material aspects. The practicality test yielded an average score of 90.13%, categorized as "Highly Practical". This learning media successfully facilitates students in understanding basic photography concepts and increases their motivation to learn through interactive features such as animations, videos, and evaluation questions. With valid and practical results, this application is suitable as an alternative learning media to support the teaching of Basic Photography at SMK Negeri 4 Padang.